Assessment of phytotoxicity of ash and slag waste from low-capacity boiler houses and individual heating systems on the example of the town Shakhtersk, Sakhalin region - Ekaterina V. Dakhova; Ludmilla P. Mayorova; Alexey I. Lukyanov (RUDN Journal of Ecology and Life Safety, 2022)
The relevance of the work is due to the study of the issue of disposal and possible use of ash and slag waste in small towns, in particular in the Far East, where the predominant types of heating are low-power boilers or individual heating systems. The simplest and clearest methods for assessing the impact of generated waste on the environment are bioindicative methods, in particular, the assessment of phytotoxicity. The analysis of the phytotoxic effect of ash and slag wastes of various origins and different periods of storage, as well as coal samples in the conditions of urban settlements, was carried town Shakhtersk, Sakhalin region, in relation to herbaceous plants of various systematic groups in the framework of a number of laboratory experiments. The phytotoxic effect of the considered samples was determined by comparing the parameters of the test function of the control and experimental seeds. The dependence of the magnitude of the phytotoxic effect on the shelf life and the type of origin of ash and slag waste is shown. The data obtained are the basis for carrying out additional experiments and studies, as well as determining the chemical composition of the samples under consideration.